Application of Artificial Neural Network for Forecasting Nitrate Concentration as a Water Quality Parameter: A Case Study of Feitsui Reservoir, Taiwan - Latif S.D.; Azmi M.S.B.N.; Ahmed A.N.; Fai C.M.; El-Shafie A. (International Information and Engineering Technology Association, 2023)
Agricultural robots; Ammonia; Biochemical oxygen demand; Dissolved oxygen; Forecasting; Forestry; Nitrates; Nitrogen oxides; Potable water; Reservoirs (water); Water quality; Water resources; Accurate modeling; Artificial neural network models; Correlation coefficient; Hydro-power generation; Industrial activities; Nitrate concentration; Nitrogen dioxides; Water quality parameters; Neural networks